Microplastics in commercial bivalves from China. (December 2015) - Li, Jiana; Yang, Dongqi; Li, Lan; Jabeen, Khalida; Shi, Huahong
Abstract: We investigated microplastic pollution in 9 commercial bivalves from a fishery market in China. Multiple types of microplastics, including fibers, fragments and pellets, occurred in the tissue of all bivalves. The number of total microplastics varied from 2.1 to 10.5 items/g and from 4.3 to 57.2 items/individual for bivalves. Scapharca subcrenata contained on average 10.5 items/g and exhibited the highest levels of microplastics by weight. Fibers were the most common microplastics and consisted of more than half of the total microplastics in each of the 8 species. In Alectryonella plicatula, pellets accounted for 60% of the total microplastics. The most common size class was less than 250 μm and accounted for 33–84% of the total microplastics calculated by species. Our results suggest that microplastic pollution was widespread and exhibited a relatively high level in commercial bivalves from China. More intensive investigations on microplastics should be conducted in seafood. Graphical abstract: Highlights: Fiber, fragment and pellet microplastics were found in 9 bivalves. The abundance of microplastics was 2.1–10.5 items/g. Fibers were the most common microplastics. The most common size class of microplastics was less than 250 μm. Microplastic pollution was widespread and serious in commercial bivalves. Abstract : Fiber, fragment and pellet microplastics in the range of 2.1–10.5 items/g were observed in 9 species of commercially popular bivalves from China.